Occupational Stress Management According to David C. Mohr: Book Review of Stress and Mood Management Program for Individuals with Multiple Sclerosis - Alkhafidhoh, Faizah; Sopingi, Imam; Hidayati, Athi’ (JIES : Journal of Islamic Economics Studies, 2025)
This article presents a book review of "The Stress and Mood Management Program for Individuals with Multiple Sclerosis" by David C. Mohr, a comprehensive guide rooted in Cognitive-Behavioral Therapy (CBT) principles. Work-related stress and psychological distress are significant challenges for individuals with Multiple Sclerosis (MS), impacting their quality of life and disease management. This book, part of the "Treatments That Work" series, offers an evidence-based approach to managing the stress, depression, and anxiety often co-occurring with MS. The program outlined in the book encompasses core CBT techniques such as cognitive restructuring, behavioral activation, social support building, and problem-solving, complemented by optional modules tailored for MS-specific issues, including fatigue management, pain, and self-injection anxiety. This review analyzes the structure, strengths, and relevance of Mohr's program as a valuable tool for mental health professionals and individuals with MS seeking self-management strategies. It highlights that the book provides a structured, research-backed framework for enhancing psychological well-being and quality of life for those living with MS.